2008
DOI: 10.1029/2008gl034071
|View full text |Cite
|
Sign up to set email alerts
|

When can we expect extremely high surface temperatures?

Abstract: In the Essence project a 17‐member ensemble simulation of climate change in response to the SRES A1b scenario has been carried out using the ECHAM5/MPI‐OM climate model. The relatively large size of the ensemble makes it possible to accurately investigate changes in extreme values of climate variables. Here we focus on the annual‐maximum 2m‐temperature and fit a Generalized Extreme Value (GEV) distribution to the simulated values and investigate the development of the parameters of this distribution. Over most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
164
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(169 citation statements)
references
References 16 publications
5
164
0
Order By: Relevance
“…The overall most consistent trends toward increases in heavier precipitation events are found in North America (Peterson et al 2008;DeGaetano 2009;Pryor et al 2009;Gleason et al 2008). Models project substantial increases in temperature extremes by the end of the 21st century with the length, frequency, and/or intensity of warm spells and heat waves increasing over most land areas (Kharin et al 2007;Sterl et al 2008;Orlowsky and Seneviratne 2012). In addition, future climate simulations generally project increases in the greatest precipitation events over northwestern and northeastern US (Meehl et al 2005).…”
mentioning
confidence: 85%
“…The overall most consistent trends toward increases in heavier precipitation events are found in North America (Peterson et al 2008;DeGaetano 2009;Pryor et al 2009;Gleason et al 2008). Models project substantial increases in temperature extremes by the end of the 21st century with the length, frequency, and/or intensity of warm spells and heat waves increasing over most land areas (Kharin et al 2007;Sterl et al 2008;Orlowsky and Seneviratne 2012). In addition, future climate simulations generally project increases in the greatest precipitation events over northwestern and northeastern US (Meehl et al 2005).…”
mentioning
confidence: 85%
“…In the ESSENCE project (Sterl et al, 2008) the ECHAM5/MPI-OM climate model (Jungclaus et al, 2006) has been used to simulate the climate from 1950 to 2100, assuming future greenhouse gas concentrations to follow the SRES A1b scenario (Nakicenovic et al, 2000). To assess the full range of internal variability and to obtain good statistics for extreme cases, 17 integrations have been done, each starting from slightly different initial conditions.…”
Section: Essencementioning
confidence: 99%
“…Existing projections of extreme (1:10,000 year) conditions with the ESSENCE ensemble (Sterl et al 2008), based on climate scenario SRES A1b, do not change with respect to present-day climate in front of the Dutch coast (see Sterl et al (2009) for storm surge levels and De for wave height and period). It is, furthermore, shown that the change in offshore wave conditions is small when the water depth is increased by 1 m; therefore, we assumed unaltered offshore wave and storm surge characteristics.…”
Section: Hydrodynamical Boundary Conditionsmentioning
confidence: 99%
“…Based on the 17-member CMIP3 ESSENCE ensemble (Sterl et al 2008), the 1:10,000-year storm surge (Sterl et al 2009) and wave extremes are not projected to change along the Dutch coast. A generalized extreme value (GEV) analysis on annual maximum daily average wind speed data from 12 general circulation models (GCMs) on two climate scenarios (RCP 4.5 and RCP 8.5) did not reveal any coherent changes in annual maximum wind speeds, or in wind speeds with lower return frequencies above the North Sea basin (De Winter et al 2013).…”
mentioning
confidence: 99%